Chemical, morphological and microhardness changes of dentine after chemomechanical caries removal. (6th August 2013) - Hamama, HH; Yiu, CKY; Burrow, MF; King, NM
Abstract: Background: This study compared the chemical, morphological and microhardness changes in carious dentine following application of NaOCl‐based (Carisolv), papain‐based (Papacarie) chemomechanical caries removal agents with conventional rotary method. Methods: Thirty‐two carious and eight non‐carious human permanent molars were used. The carious molars were randomly distributed into four groups: Group 1 (positive control) – molars were left without caries removal; Group 2 – caries excavated with rotary method; Group 3 – caries excavated with Carisolv; Group 4 – caries excavated with Papacarie. Group 5 (negative control) consisted of eight sound molars. After caries excavation, all specimens were prepared for chemical, morphological analysis and Vickers hardness testing. Results: EDX analysis showed no significant difference in Ca wt%, P wt% and Ca/P ratio among Groups 2 to 5. Vickers hardness of dentine from Groups 3 and 4 was significantly lower (p < 0.05) than for Groups 2 and 5. The use of Papacarie resulted in a dentine surface without smear layer and patent tubules, while Carisolv resulted in a dentine surface exhibiting two patterns: (1) the presence of smear layer or (2) patent tubules with partial smear layer formation. Conclusions: Papain‐based (Papacarie) chemomechanical caries removal method is a reliable alternative to conventional rotary and NaOCl‐based (Carisolv) caries removal.